Financial Letter to Members - San Luis Obispo Buddhist Temple::::::author::: (1959)
A thank you letter from the San Luis Obispo Buddhist Church to members for supporting the Painting Fund Drive: "Dear Members: The San Luis Obispo Buddhist Church extends its sincere appreciation for your generous support in the recent Painting Fund Drive. We enclose our financial report together with the list of donors. Due to your generous response, the Church was able to realize a substantial balance from this drive. With gassho, S.L.O. Buddhist Church".